PEMBINAAN SANTRI PONDOK PESANTREN ROFIATUL ISLAM DALAM PERHITUNGAN DANA ZAKAT SESUAI SYARIAT - Alvan Fathony (Politeknik Negeri Sriwijaya, 2023)
The purpose of implementing community service (PKM) is to provide assistance in the management and calculation of zakat funds according to Islamic law for Rofiatul Islam students. Santri who are service partners are Rofiatul Islam students, Sentong Village, Krejengan District, Probolinggo Regency. The implementation of this service is fully supported by the Caregivers of the Rofiatul Islam Islamic Boarding School. The method of implementing this service is carried out with a tutorial on zakat material which is followed by an intensive two-way discussion, and at the end of the implementation of the service a demonstration of zakat calculations is carried out for 4 (four) meetings. The time for carrying out this community service is the odd semester of 2022/2023 during December-March 2023. The place for carrying out the community service is on the terrace of the Rofiatul Islam jami mosque. The results of this service show that the assistance in the management and calculation of zakat funds according to Islamic law provides a deeper understanding of the procedures for managing and calculating zakat funds for Rofiatul Islam students in Sentong Village, Krejengan District, Probolinggo Regency. The implications of this community service activity make the management of zakat funds properly according to the guidelines given by Islamic law, making zakat funds maximally productive and on target for recipients